Answer:
y = -2x/3 + 6
Step-by-step explanation:
y = mx+b
m = y2-y1/x2-x1
m = 2 - 6/6 - 0
m= -4/6 = -2/3
b = y-intercept = 6
How much would $600 be worth after 10 years, if it were invested at 4% interest compounded continuously? (Use the formula below and round your answer to the nearest cent.)
A(t)=P•e^rt
Answer:
$895.09
Step-by-step explanation:
Applying the given formula:
A = $600e^(0.04*10), or
= $895.09
We find that the answer is $895.09.
Compound interest is interest calculated on the initial principal, which also includes all of the accumulated interest from the previous.
How to find how much would $600 be worth after 10 years, if it were invested at 4% interest compounded continuously?
Hint: Use the formula below and round your answer to the nearest cent.)
A(t)=P•e^rt.
Applying the given formula:
A = $600e^(0.04*10),
or
= $895.09.
Learn more about references on: https://brainly.com/question/18456266
#SPJ2
WILL GIVE BRAINLEIST NEED TO TURN IN BY 9 P.M. PLS HURRY SUPER EASYIdentify the equation that does not belong with the other three. Explain your reasoning.
A. 6+x=9 B. 15=x+12 C. x+9=11 D. 7+x=10
Answer:
C. x + 9 = 11
Step-by-step explanation:
We are trying to identify which of the equations does not match with the others. In this case, solve for x in each equation:
Option A):
6 + x = 9
Subtract 6 from both sides:
6 (-6) + x = 9 (-6)
x = 9 - 6
x = 3
Option B):
15 = x + 12
Subtract 12 from both sides:
15 (-12) = x + 12 (-12)
15 - 12 = x
x = 3
Option C):
x + 9 = 11
Subtract 9 from both sides:
x + 9 (-9) = 11 (-9)
x = 11 - 9
x = 2
Option D):
7 + x = 10
Subtract 7 from both sides:
x + 7 (-7) = 10 (-7)
x = 10 - 7
x = 3
---------------------------------------------------------------------------------------------------------
As you can tell, all the equations end with x = 3 as there answers except C. x+9=11, making (C) your answer.
~
The time it takes to read a book depends on the number of pages in the book
The situation "The time it takes to read a book depends on the number of pages in the book" in function notation is: A. Time(pages).
In Mathematics, a function is typically used in mathematics for uniquely mapping an input variable (domain or independent value) to an output variable (range or dependent value).
This ultimately implies that, an independent value represents the value on the x-axis of a cartesian coordinate while a dependent value represents the value on the y-axis of a cartesian coordinate.
In this context, we can logically deduce that time is a function of the number of pages, so it should be written in function notation as follows:
Time(pages).
Complete Question:
Which of the following shows the situation below in function notation?
The time it takes to read a book depends on the number of
pages in the book.
A. Time(pages)
B. Book(pages)
C.Pages(time)
D. Book(time)
Find the shortest distance from A to C in the diagram below.
Answer:
The shortest distance from A to C is [tex]AC=5\sqrt{13}\ units[/tex]
Step-by-step explanation:
see the attached figure to better understand the problem
we know that
The shortest distance from A to C is the hypotenuse of the right triangle AYC
Applying the Pythagoras Theorem
[tex]AC^{2}=AY^{2} +YC^{2}[/tex]
step 1
Find the length YC (hypotenuse of the right triangle YBC)
Applying the Pythagoras Theorem
[tex]YC^{2}=YB^{2} +BC^{2}[/tex]
substitute the given values
[tex]YC^{2}=6^{2} +15^{2}[/tex]
[tex]YC^{2}=261[/tex]
[tex]YC=\sqrt{261}\ units[/tex]
step 2
Find the shortest distance from A to C
[tex]AC^{2}=AY^{2} +YC^{2}[/tex]
substitute the given values
[tex]AC^{2}=8^{2} +\sqrt{261}^{2}[/tex]
[tex]AC^{2}=325[/tex]
[tex]AC=\sqrt{325}\ units[/tex]
[tex]AC=5\sqrt{13}\ units[/tex]
Mary Stevens earns $6 an hour at her job and she is entitled to time and a half for overtime and double time on holidays. Last week she worked 40 hours of regular time ,6 1/2 hours of over time and 8 hours of holiday time. how much did she earn?
Answer:
$394.5
Step-by-step explanation:
40 x 6 = 240
6.5 x 9 = 58.5
(6 x 2) x 8 = 96
240 + 58.5 + 96
If seamstress is paid 7.85 per hour and works 18.75 hours in one week, how much is she paid in one week?
PLEASE HELP AGAIN WILL MARK BRAINLEST !!!!!
Answer:
3
Step-by-step explanation:
g(-1) means what is g(x) when x=-1.
So find -1 under the column labeled x and then scroll directly to the right of that and you should see what g(-1). It is 3
Here are my examples:
g(-8)=6
g(-5)=-2
g(-1)=3
g(0)=-5
[tex]x^{2} - x - 6 \div {x}^{2} - 4[/tex]
[tex]\bf x^2-x-6\div x^2-4\implies \cfrac{x^2-x-6}{x^2-4}\implies \cfrac{(x-3)(x+2)}{\underset{\textit{difference of squares}}{x^2-2^2}} \\\\\\ \cfrac{(x-3)~~\begin{matrix} (x+2) \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}{(x-2)~~\begin{matrix} (x+2) \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}\implies \cfrac{x-3}{x-2}[/tex]
A rectangle is enlarged by a factor of 6 that originally has the area of 20in squared. What is the area of the enlarged rectangle?
A: 120in squared
B: 720in squared
C: 2,400in squared
D: 14,400in squared
Answer:
The person on top is wrong the answer is 14,400 in.² or D
Step-by-step explanation:
The correct option is B. 720in squared. The area of the rectangle, when enlarged by a factor of 6, scales by the square of 6, resulting in an enlarged area of 720 square inches.
To determine the area of a rectangle after it has been enlarged by a factor, we need to understand how area scales with respect to the linear dimensions. When a shape is enlarged by a factor, the area scales by the square of that factor.
Given:
→ Original area = 20 square inches
→ Enlargement factor = 6
Steps to Find the Enlarged Area:
→ Calculate the scaling factor for the area:
= 6²
= 36.
→ Multiply the original area by this scaling factor:
= 20 in² * 36
= 720 in².
Therefore, the area of the enlarged rectangle is 720 square inches, which corresponds to answer choice B.
If x= sin theta then x/√1-x^2 is
Well,
Given that [tex]x=\sin(\theta)[/tex],
We can rewrite the equation like,
[tex]\dfrac{\sin(\theta)}{\sqrt{1-\sin(\theta)^2}}[/tex]
Now use, [tex]\cos(\theta)^2+\sin(\theta)^2=1[/tex] which implies that [tex]1-\sin(\theta)^2=\cos(\theta)^2[/tex]
That means that,
[tex]\dfrac{\sin(\theta)}{\sqrt{1-\sin(\theta)^2}}\Longleftrightarrow\dfrac{\sin(\theta)}{\sqrt{\cos(\theta)^2}}[/tex]
By def [tex]\sqrt{x^2}=x[/tex] therefore [tex]\sqrt{\cos(\theta)^2}=\cos(\theta)[/tex]
So the fraction now looks like,
[tex]\dfrac{\sin(\theta)}{\cos(\theta)}[/tex]
Which is equal to the identity,
[tex]\boxed{\tan(\theta)}=\dfrac{\sin(\theta)}{\cos(\theta)}[/tex]
Hope this helps.
r3t40
What is the product of (3a + 2)(4a? - 2a + 9)?
1223 - 2a + 18
12a3 + 6a +9
12a3 - 6a+ 23a + 18
1223 + 2a + 23a + 18
Answer:
The answer is 12a^3+2a²+23a+18 ....
Step-by-step explanation:
The given terms are:
(3a + 2)(4a² - 2a + 9)
Now multiply each value of second bracket with the first bracket:
=4a²(3a+2) -2a(3a+2)+9(3a+2)
=12a^3+8a²-6a²-4a+27a+18
Solve the like terms:
=12a^3+2a²+23a+18
Therefore the answer is 12a^3+2a²+23a+18 ....
Which equation is y=9x^2+9x-1 re-written in vertex form
Answer:
A. y = 9(x +1/2)^2 - 13/4.
Step-by-step explanation:
y = 9x^2 + 9x - 1
y = 9(x^2 + x) - 1
y = 9 [ (x + 1/2)^2 - 1/4] - 1
y = 9 (x + 1/2)^2 - 9/4 - 1
y = 9(x +1/2)^2 - 13/4.
Answer: First Option
[tex]y = (x+\frac{1}{2}) ^ 2 -\frac{13}{4}[[/tex]
Step-by-step explanation:
For a quadratic function of the form:
[tex]y = ax ^ 2 + bx + c[/tex]
The vertex form of the equation is:
[tex]y = (x-h) ^ 2 + k[/tex]
Where the vertex is the point (h, k) and [tex]h =-\frac{b}{2a}[/tex]
In this case the equation is: [tex]y=9x^2+9x-1[/tex]
So:
[tex]a=9\\b=9\\c=-1[/tex]
Therefore:
[tex]h =-\frac{9}{2*(9)}[/tex]
[tex]h =-\frac{1}{2}[/tex]
[tex]k=9(-\frac{1}{2})^2+9(-\frac{1}{2})-1\\\\k=-\frac{13}{4}[/tex]
Finally the equation in vertex form is:
[tex]y = (x+\frac{1}{2}) ^ 2 -\frac{13}{4}[[/tex]
Some people might be confused while applying the three theorems related to segments in circles. They might not be sure which segments to multiply. What helpful hints would you recommend they use to figure out which segments to multiply for each of the three theorems?
Answer:
1.Intersecting segments theorem
In this scenario, two secant segments intersect each other inside the circle.The relationship is that the product of the segment pieces of one segment is equal to the product of the segment piece of the other.
Hint⇒identify the corresponding segment pieces for multiplication
2.Two secant segments that intersect outside circle
In this scenario the product of the whole secant with its external part is equal to the product of the other whole secant segment with its external part.
Hint ⇒identify the segment pieces outside the circle and the whole segments that include the external parts
3.One secant and one Tangent
In this case, the relation is that the product of whole segment with its external part is equal to square of the tangent segment.
Hint⇒ Identify the tangent segment and the whole secant segment that has an external part.
Hope this Helps.
the measure of angle 6 =(11x +8) degrees and measure of angle 7(12x-4)degrees what is the measure of angle 4
40
48
132
140
Answer:
Answer is m∠4=40
Step-by-step explanation:
According to the image which i have posted below,we first want to take note that m∠6 & m∠7 are vertical angles. Vertical angles are equal to each other, therefore m∠6 is equal to m∠7.
m∠6 = m∠7 (vertical angles)
11x + 8 = 12x – 4
12x - 11x = 8 + 4
x = 12
so
m∠6 = 11x + 8
m∠6 = 11(12) + 8
m∠6 = 132 + 8
m∠6 = 140
m∠4 = 180 - m<6
m∠4 = 180 - 140
m∠4 = 40
Answer is m∠4=40....
how do i solve 3/-2 x = 24
Answer:
x = -16
Step-by-step explanation:
3
(— • x) - -24 = 0
2
-24 -24 • 2
-24 = ——— = ———————
1 2
For this case we must solve the following equation:
[tex]\frac {3} {- 2x} = 24[/tex]
Multiplying by 2x on both sides of the equation:
[tex]-3 = 24 * 2x\\-3 = 48x[/tex]
Dividing between 48 on both sides of the equation:
[tex]x = - \frac {3} {48}[/tex]
We simplify:
[tex]x = - \frac {1} {16}[/tex]
Answer:[tex]x = - \frac {1} {16}[/tex]
I filled 6/9 of the prescriptions for the pharmacist to review. The pharmacist returns and reviews 2/3 of the prescriptions. How many more prescriptions does the pharmacist have left to review that I filled?
[tex]\left(1-\dfrac{2}{3}\right)\cdot\dfrac{6}{9}=\dfrac{1}{3}\cdot \dfrac{2}{3}=\dfrac{2}{9}[/tex]
The pharmacist has 2 more prescriptions left to review that you filled.
To find out how many prescriptions the pharmacist has left to review, we can follow these steps:
1. Calculate the total number of prescriptions filled by you:
[tex]\[ \text{Total filled prescriptions} = \frac{6}{9} \times \text{Total prescriptions} \][/tex]
2. Calculate the number of prescriptions reviewed by the pharmacist:
[tex]\[ \text{Prescriptions reviewed by pharmacist} = \frac{2}{3} \times \text{Total filled prescriptions} \][/tex]
3. Calculate the number of prescriptions left for the pharmacist to review:
[tex]\[ \text{Prescriptions left to review} = \text{Total filled prescriptions} - \text{Prescriptions reviewed by pharmacist} \][/tex]
Let's put the numbers into these equations. Assuming there were initially 9 prescriptions:
1. Total filled prescriptions:
[tex]\[ \text{Total filled prescriptions} = \frac{6}{9} \times 9 = 6 \][/tex]
2. Prescriptions reviewed by pharmacist:
[tex]\[ \text{Prescriptions reviewed by pharmacist} = \frac{2}{3} \times 6 = 4 \][/tex]
3. Prescriptions left to review:
[tex]\[ \text{Prescriptions left to review} = 6 - 4 = 2 \][/tex]
Evaluate 5(x - 1) - 2 when x = 3.
O A. -4
Ос.
O D.O
Answer:
8
Step-by-step explanation
First you have to plug in 3 for x:
5(3-1)-2
Then using PEMDAS you would simplify that:
5(2)-2
10-2
8
What is the equation in point slope form of the line passing through (-2,0) and (2,8)?
Answer:
y - 8 = 2(x - 2)Step-by-step explanation:
The point-slope of an equation of a line:
[tex]y-y_1=m(x-x_1)[/tex]
m - slope
The formula of a slope:
[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]
We have the points (-2, 0) and (2, 8).
Substitute:
[tex]m=\dfrac{8-0}{2-(-2)}=\dfrac{8}{4}=2[/tex]
for the point (-2, 0):
[tex]y-0=2(x-(-2))\\\\y-0=2(x+2)[/tex]
for the point (2, 8):
[tex]y-8=2(x-2)[/tex]
Given a=8, b=7 and c =6, use the law of cosines to solve the triangle for the value of C. Round answer two decimal.
a. 80.44
b. 46.57
c. 57.91
d. 75.52
Answer:
B) 46.67°
Step-by-step explanation:
Step 1 : Write the cosine formula to find the angle C
c² = a² + b² - 2ab cos C
Step 2 : Substitute the values in the formula
6² = 7² + 8² - 2(8)(7) cos C
cos C = 0.6875
C = cos^-1 (0.6875)
C = 46.567 °
Step 3 : Round off to 2 decimal places
Angle C = 46.57°
!!
Scarlett is designing a package for a candy her company makes. She has cut several cardboard equilateral triangles, squares, rectangles, and regular pentagons to try out her ideas for the package. Which 3-D figure and combination of shapes can Scarlett use? Equilateral triangle prism with one triangle and three rectangles Pentagonal prism with one pentagon and five rectangles Rectangular prism with four rectangles Square prism with six squares
Answer:
it would be the 4th option
Step-by-step explanation:
all the above are wrong except the fourth option because a 3-D square or cube is made up of 6 equal squares. I hope this helps a-lot. : )
The 3-D figure Scarlett can make and the combinations of shapes she can use is a square prism with six squares.
What is a square prism?
A square prism is a three-dimensional object that is made up of six squares.
The volume of a square prism = length x width x height.
To learn more about right square prism, please check: https://brainly.com/question/13048128
What is the relationship between the values of m and n plotted on the number line below?
On a plotted graph, 'm' commonly represents the slope indicating how much the line rises or falls for each step across. On the other hand, 'n' usually demonstrates the y-intercept - the point where the line crosses the y-axis.
Explanation:The relationship between the values of m and n plotted on a number line depends on the mathematic law or concept being applied. But in many cases, such as on a graph, 'm' typically represents the slope while the 'n' value shows the y-intercept.
Slope (m) shows how much a line moves up or down along the y-axis for each step across the x-axis ('run'). The equation for this is ∆y/∆x meaning the change in y over the change in x. For example, if the slope (m) is three, each time the x value increases by one, the y value will rise by three.
The y-intercept (n) is the point where the line crosses the y-axis. This is the value of y when x = 0.
Learn more about Slope and Y-Intercept here:https://brainly.com/question/19824331
#SPJ12
The average speed of Car 1 = 45 mph.
The average speed of Car 2 = 65 mph.
Time elapsed between the start of Car 1 and start of Car 2 = 18 minutes.
How long before Car 2 overtakes Car 1? ____ hour.
Answer:
[tex]\boxed{\text{0.675 h}}[/tex]
Step-by-step explanation:
18 min = 0.3 h
Car 1 started 0.3 h before Car 2.
Let t = time of Car 2. Then
t + 0.3 = time of Car 1
Distance = speed × time, and both cars travel the same distance. Then
[tex]\begin{array}{rcl}45(t + 0.3) & = & 65t\\45t + 13.5 & = & 65t\\20t & = & 13.5\\t & = & \textbf{0.675 h}\\\end{array}\\\text{Car will overtake Car 1 in } \boxed{\textbf{0.675 h}}[/tex]
Check:
[tex]\begin{array}{rcl}45(0.675 + 0.3) & = & 65 \times 0.675\\45 \times 0.975 & = & 43.875\\43.875 & = & 43.875\\\end{array}[/tex]
OK.
Answer:
Car2 overtakes Car1 after 0.675 hours
Step-by-step explanation:
To solve this question, we must know that
Speed = distance / time
Speed_car1 = 45 mph = distance_car1/ time_1
Speed_car2= 65 mph = distance_car2/ time_2
We know that
time1 - time2 = 18 minutes = 0.3 h
And, at the time of the overtake, both cars will have traveled the same distance.
So,
distance_car1 = 45 mph * time1 = distance_car2 = 65 mph * time2
time1 / time2 = 65/45
time1 = 1.444*time2
Then,
1.444*time2- time2 = 0.3 h
time2 = 0.675 h
time1 = 0.975 h
Car2 overtakes Car1 after 0.675 hours
What is tan 45º?
help me plzzzx
Answer:
Tangent of 45º When a square is divided by a diagonal into two equal right triangles, the angles measure 90º, 45º and 45º. The diagonal (hypotenuse of the triangle) is then obtained by applying the Pythagorean theorem: Trigonometric Ratios. Trig.
Step-by-step explanation:
The graph shows the distance Kerri drives on a trip. What is Kerri's speed?
Answer:
kerri's speed is 50 MPH (miles per hour)
Step-by-step explanation:
You look at the one, and follow the line upward until it stops, and that shows the speed, per hour. I know thats correct so i hope this helps you and good luck on the rest of the test :)
Answer:
50 miles per hour.
Step-by-step explanation:
In this graph, distance covered by Kerri has been shown on y-axis and time on x-axis.
Speed of Kerri will be defined by the rate of change in distance which is slope of the line.
Speed = [tex]\frac{\text{change in distance}}{\text{change in time}}[/tex]
= [tex]\frac{300-0}{6-0}[/tex] = 50 miles per hour.
Factor 3h2 – 11h - 42
A. (3h – 7)(h + 6)
B. 3(h + 7)(h - 6)
C. (34 – 6)(h + 7)
D. (3h + 7)(h – 6)
Answer:
The correct answer is option D. (3h + 7)(h – 6)
Step-by-step explanation:
It is given a quadratic function ,
3h² - 11h - 42
To find the factors of given function
3h² - 11h - 42 = 3h² - 18h + 7h - 42
= 3h(h -6) + 7(h - 6)
=(h - 6)(3h + 7)
= (3h + 7)(h – 6)
The correct answer is option D. (3h + 7)(h – 6)
Match the system of equations to their solutions
Answer:
x=2, y=7 -------> y=11-2x and 4x-3y=-13
x=5, y=2 ------> 2x+y=12 and x=9-2y
x=3, y=5 -----> 2x+y=11 and x-2y=-7
x=7, y=3 ------> x+3y=16 and 2x-y=11
Step-by-step explanation:
Part 1) we have
2x+y=12 -----> equation A
x=9-2y -----> equation B
Solve by substitution
Substitute equation B in equation A and solve for y
2(9-2y)+y=12
18-4y+y=12
4y-y=18-12
3y=6
y=2
Find the value of x
x=9-2(2)=5
therefore
The solution is
x=5, y=2
Part 2) we have
x+2y=9 -----> equation A
2x+4y=20 ---> equation B
Multiply equation A by 2 both sides
2(x+2y)=9*2
2x+4y=18 -----> equation C
Compare equation C with equation B
Both equations have the same slope with different y-intercept
therefore
The lines are parallel and the system has no solution
Part 3) we have
x+3y=16 ------> equation A
2x-y=11 -----> equation B
Solve the system by elimination
Multiply equation B by 3 both sides
3(2x-y)=11*3
6x-3y=33 -----> equation C
Adds equation A and equation C
x+3y=16
6x-3y=33
----------------
x+6x=16+33
7x=49
x=7
Find the value of y
x+3y=16
7+3y=16
3y=16-7
3y=9
y=3
therefore
The solution is
x=7, y=3
Part 4) we have
y=11-2x -----> equation A
4x-3y=-13 ---> equation B
Solve by substitution
Substitute equation A in equation B and solve for x
4x-3(11-2x)=-13
4x-33+6x=-13
10x=-13+33
10x=20
x=2
Find the value of y
y=11-2(2)=7
therefore
The solution is
x=2, y=7
Part 5) we have
y=10+x -----> equation A
-3x+3y=30 ---> equation B
Multiply equation A by 3 both sides
3*y=3*(10+x)
3y=30+3x
Rewrite
-3x+3y=30 ----> equation C
equation B and equation C are identical
therefore
The system has infinitely solutions
Part 6) we have
2x+y=11 -----> equation A
x-2y=-7 ----> equation B
Solve by elimination
Multiply equation A by 2 both sides
2(2x+y)=11*2
4x+2y=22 ----> equation C
Adds equation B and equation C and solve for x
x-2y=-7
4x+2y=22
----------------
x+4x=-7+22
5x=15
x=3
Find the value of y
x-2y=-7
3-2y=-7
2y=3+7
2y=10
y=5
therefore
The solution is
x=3, y=5
If P(A) = 0.60 and P(B) = 0.20, then A and B are independent events if
Answer:
[tex]P(A\cap B)=0.12[/tex]
Step-by-step explanation:
If two events, A and B are independent, then [tex]P(A\cap B)=P(A)\times P(B)[/tex], otherwise the two events are dependent.
If P(A)=0.60 and P(B) =0.20, then A and B are independent events, if
[tex]P(A\cap B)=0.60\times 0.20[/tex]
[tex]\implies P(A\cap B)=0.12[/tex]
Therefore the best complete is:
If P(A) = 0.60 and P(B) = 0.20, then A and B are independent events if [tex]P(A\cap B)=0.12[/tex]
Answer:
Step-by-step explanation:
p(a and b) = 0.12
The second number in an ordered pair of numbers that corresponds to a point on a coordinate system is the ?
Answer:
See below.
Step-by-step explanation:
The y-coordinate , giving the value of the function at this point. It is a part of the range of the function.
Answer:
It is the y-value
Step-by-step explanation:
Took the test on edg.
A recipe calls for 3 1/2 cups of sugar. If you want to make only 1/3 of the recipe, how much sugar should you use?
Answer: 1 1/6 cups of sugar
Step-by-step explanation:
First let’s convert 3 1/2 into an improper fraction: 7/2
Then we multiply 7/2 by 1/3: 7/2*1/3=7/6
Then finally we convert 7/6 into a mixed number, so your answer will be 1 1/6
One third of the sum of 5 times a number and 3 is less than one fourth the sum of six times that number and 5
Answer:
x < 3/2.
Step-by-step explanation:
1/3( 5x + 3) < 1/4(6x + 5)
5/3 x + 1 < 3/2x + 5/4
5/3 x - 3/2 x < 5/4 - 1
1/6 x < 1/4
x < 6/4
x < 3/2.
The value of the variable x is less than 3/2.
What is the solution to the equation?The distribution of weights to the variables involved that establishes the equilibrium in the calculation is referred to as a result.
Let x be the number.
One-third of the sum of 5 times a number and 3 is less than one-fourth the sum of six times that number and 5. Then the equation will be
(1/3)(5x + 3) < (1/4)(6x + 5)
Simplify the inequality, then the value of x will be
20x + 12 < 18x + 15
2x < 3
x < 3/2
The value of the variable x is less than 3/2.
More about the solution of the equation link is given below.
https://brainly.com/question/545403
#SPJ2